REFORM OF THE RUSSIAN ANTI-CORRUPTION LEGISLATION: OECD ECONOMIC CONDITION OR LEGAL IMPORTANCE - E. L. Sidorenko (Vestnik MGIMO-Universiteta)
In this paper we define the prospects for the criminalization of promises and offers a bribe to a foreign official or an official of a public international organization in the Russian criminal law. Despite the increased interest in the problem of implementation of international law in the national legal system, many aspects of the topic studied. These include punishment, the possibility of establishing criminal liability for bribery. OECD anti-corruption standards considered in working with three positions: through Russia ratified the convention, through the analysis of the experience of the criminalization of bribery of foreign public officials in foreign legislation and from the perspective of the established system of national criminal and administrative law. The paper presents a systematic analysis of the proposal and the promise of a bribe as socially dangerous acts. Refined methods of implementation of anti-corruption standards in the Russian legislation. Problems has led to widespread use of the system, comparative law and documentary approaches. The paper concludes formulate concrete proposals to improve the criminal law and identifies strategic directions of modern anti-corruption policy.